Studi In Vitro Permukaan Glass Ionomer Cement Setelah Perendaman dalam Minuman Bersoda dengan Gula Buatan - Irsan Ibrahim Lubis; Eddy Kosasih (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2021)
Carbonated soft drinks (soda) are often consumed by the world community including Indonesia by all people, both young and old. The high sugar content in soft drinks can increase blood sugar if consumed continuously. In addition, soft drinks with artificial sugar have a higher acidity than regular sugar. With such a high level of acidity and continuous consumption, tooth surface roughness can decrease. One of the most frequently used restorative materials in Indonesia is Glass Ionomer Cement (GIC) because it is easy to manipulate and binds directly to enamel and dentin. The purpose of this study was to determine the effect of consuming soft drinks with artificial sugar on GIC restoration materials. Thirty GIC specimens with a diameter of 6 x 2 mm were immersed in mineral water and Diet Coke for 24 hours. Before and after immersion, the specimens were examined with a surface hardness test, scanning electron microscope and analytical scales. Data analysis used paired t test and kruskall wallis. From the paired t-test statistical test, there was a significant difference between the percentage reduction in weight of the GIC sample after immersion in water with Diet Coke. The Kruskal Wallis test results showed that there was a significant difference in the roughness value of GIC immersed in mineral water with Diet Coke. The pH of carbonated drinks with artificial sugar (Diet Coke) below the critical pH (5.5) can affect the solubility of the GIC specimens, thereby giving changes in surface roughness, changes in weight and changes in surface morphology of GIC specimens.